Challengers [videorecording (DVD)] - Kuritzkes, Justin; Zendaya, 1996-; O'Connor, Josh; Faist, Mike; Mukdeeprom, Sayombhu; Reznor, Trent; Ross, Atticus, 1968- (Warner Bros. Entertainment Inc., 2024)
A former tennis prodigy turned coach and a force of nature who makes no apologies for her game on and off the court. Married to a champion on a losing streak, Tashi's strategy for her husband's redemption takes a surprising turn when he must face off against the washed-up Patrick, his former best friend, and Tashi's former boyfriend. As their pasts and presents collide, and tensions run high, Tashi must ask herself, what will it cost to win?